Beneficial traits of grain-residing endophytic communities in wheat with different sensitivity to Pseudomonas syringae - Pastoshchuk, A.; Yumyna, Y.; Zelena, P.; Nudha, V.; Yanovska, V.; Kovalenko, M.; Taran, N.; Patyka, V.; Skivka, L. (Regulatory Mechanisms in Biosystems, 2021)
Deep insight into compositional and functional features of endophytic bacterial communities residing in wheat grains opens the way to the use of their plant growth promoting and biocontrol abilities in agricultural biotechnology. The aim of this work was to compare grain-residing endophytes from winter wheat varieties with different sensitivity to Pseudomonas syringae pv. atrofaciens (McCulloch) and to examine their plant-beneficial traits and antagonistic effects. Grain-residing bacteria were isolated from surface-sterilized grains of three wheat varieties sown in Ukraine following a culture-dependent protocol, and were screened for their plant growth promotion (PGP) and antagonistic properties. Bacterial morphotypes were represented by gram-negative rods, endospore-forming bacilli and gram-positive cocci. Different resistance to phytopathogenic pseudomonads was associated with distinctive quantitative and functional features of grain-residing endophytic communities. High resistance to P. syringae was coupled with the prevalence of gram-negative rods in the endophytic community, the highest proportion of endophytic bacteria possessing three PGP activities (phosphate solubilization, nitrogen fixation and production of indolic compounds) simultaneously, and with the most potent antagonistic activity of grain-residing endospore-forming bacilli. In total, five grain-residing isolates, which were obtained from three wheat varieties (two isolates from varieties with medium and high resistance and one – from a low-resistant variety), demonstrated ability to restrain P. syringae pv. atrofaciens (McCulloch) growth. Two isolates (P6 and P10) which were obtained from the high-resistant wheat variety Podolyanka and were assigned to Paenibacillus and Brevibacillus genera according to their biochemical profiling and MS-DS identification, showed the most potent antagonistic effects as indicated by maximum inhibition zone in agar well diffusion assay. These results shed light on the association of the features of grain-residing endophytic bacteria with wheat resistance to phytopathogenic pseudomonads. Isolates from the high-resistant wheat variety can be recommended for grain dressing as plant growth promoting and biocontrol agents for P. syringae pv. atrofaciens (McCulloch).